THE EFFECT OF THE APPLICATION OF TEAM GAMES TOURNAMENT ON PAI LEARNING INTEREST IN SMP NEGERI 2 CIPANAS CIANJUR - Nur Mala Hayati; Muhyani Muhyani; Sutisna Sutisna (Universitas Labuhanbatu, 2023)
In the era of globalization, juvenile delinquency is increasing. One reason is the low awareness of religion. Teachers as educators can suppress juvenile delinquency by increasing students' interest to learn PAI (Islamic Religious Education). In school learning activities, educators can choose a variety of methods, one of which is the TGT (Team Games Tournament). This study aims to determine a significant increase between students' learning interest that is applied and that is not applied to the TGT learning model for class IX SMPN 2 Cipanas. This research method is a quasi-experimental design and pre-test and post-test groups. Data collection techniques using questionnaires and documentation. The results of the data show t_count = 3.824 and t_table = 2.042 with a significance of 0.000 <0.005 which is the result of the t-test. the conclusion of the results of the hypothesis test is accepted